Literasi Keuangan Anak Usia Dini melalui Menabung dengan Celengan Daur Ulang Kreatif - Fransika, Widya; Mustika, Uray Ndaru; Rafida, Siti Jihan; Christina, Christina; Patricia, Cindy; Fatmi, Mutia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This community service aims to improve children’s financial literacy from an early age through socialization activities and creative training at SDN 27 Cempedak. The lack of students’ understanding of the importance of saving serves as the background for the need for enjoyable and practical financial education. The activities carried out include socialization about the benefits and purposes of saving, as well as training in making piggy banks from recycled materials such as plastic bottles, decorative paper, and origami paper as learning media. The implementation method uses a participatory and interactive approach that directly involves students. The results of the activities showed an increase in students’ understanding of the concept of saving, the emergence of motivation to set aside pocket money, and the development of creativity through handicraft activities. This program has had a positive impact in instilling the habit of saving, fostering a frugal and independent character, and introducing the concept of simple financial planning from an early age. It is expected that this activity can continue to be developed into a positive culture in schools with the support of active roles from both parents and the school.